1985
DOI: 10.1002/jnr.490130307
|View full text |Cite
|
Sign up to set email alerts
|

Taurine deficiency in the developing cat: Persistence of the cerebellar external granule cell layer

Abstract: Dietary taurine deprivation adversely affects feline pregnancy and is associated with the frequent occurrence of fetal resorption, abortion, stillbirth, and low birthweight of live kittens at term. Taurine-deprived, live-born kittens have a poor postnatal survival rate and grow less well than kittens from taurine-supplemented queens. The postnatal dietary taurine intake of such kittens is reduced if they are nursed by their biologic mothers; the concentration of taurine in milk of taurine-deprived mothers is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(64 citation statements)
references
References 23 publications
4
59
0
1
Order By: Relevance
“…6 disrupts normal radial migration. Because taurine inhibits KCC2 activation, our results using a taurine-insensitive KCC2 mutant may support previous studies showing that taurine-deficient kittens exhibit abnormalities in neuronal migration in the visual cortex and the external granule cell layer of the cerebellum (32,33).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…6 disrupts normal radial migration. Because taurine inhibits KCC2 activation, our results using a taurine-insensitive KCC2 mutant may support previous studies showing that taurine-deficient kittens exhibit abnormalities in neuronal migration in the visual cortex and the external granule cell layer of the cerebellum (32,33).…”
Section: Discussionsupporting
confidence: 90%
“…Taurine is a candidate due to enrichment in immature neurons during cerebral cortex development (30,31). In addition, taurine-deficient kittens show abnormal neuronal migration in the cerebral cortex and cerebellum (32,33). We observed that ectopically expressed KCC2 is suppressed by taurine in the embryonic brain and becomes functional in postnatal brains.…”
mentioning
confidence: 70%
“…[21][22][23] Studies have demonstrated that taurine and the taurine transporter play an important role in kidney development. 24,25 In the F1 generation of inbred taurine-deficient cats, taurine deficiency results in renal malformation, with significantly diminished renal size and progressive kidney damage. 15 In mammals, the taurine total body pool is controlled at the site of the S3 segment of the renal proximal tubule through renal adaptive regulation of the taurine transporter gene.…”
Section: Discussionmentioning
confidence: 99%
“…12 In female domestic cats, taurine depletion severely compromises reproductive performance, including an increase in fetal resorption, abortion, and stillbirth. 26 Live-born kittens demonstrate numerous neurologic abnormalities, low birth weight, and poor postnatal survival rate caused by inadequate maternal lactation. 26 The domestic cat's minimum taurine requirement was studied, 5,23 and a taurine content of 500 mg/kg dry matter of the diet was adequate for pregnancy in cats.…”
Section: Protein and Amino Acidsmentioning
confidence: 99%